Ludwig A. Feuerbach (1804-1872): Sang Peniup Terompet Ateisme - Mohammad Nabil (Himpunan Peminat Ilmu-Ilmu Ushuluddin (HIPIUS), 2013)
Feuerbach is considered as a creator of philosophical basis on atheism. Even though based on Germany idealism, mainly on Hegel, Feuerbach even refused Hegel’s concept of demythology or rationalization for Christianity faith, since the concept is regarded as religious victory over philosophy, or similar to cover Christian theology with philosophy dress. Feuerbach, consequently, established a new philosophy, a project which bases on a concept of human being (I) who would be noteworthy when there is another human being (Thou), to reject the eixistence of God and religion. For believe in God and religion is actually man’s belief in infinity and perfectness, hence, Feuerbach made ‘human togetherness’ as the infinity to replace God’s and religion’s position.